Breakdown of the quantum Hall effect in an electron-hole system - Takashina, K; Nicholas, R; Kardynal, B; Mason, N; Maude, D; Portal, J (2001)
We examine the edge states picture as applied to the electron-hole system, and show that compensated quantum Hall states are fundamentally different to quantum Hall states of single carrier type systems. Measurements of their current driven breakdown are described, and we show that these states have very small breakdown currents. (C) 2001 Elsevier Science B.V. All rights reserved.